Do Structural Breaks Affect Portfolio Designs and Hedging Strategies? International Evidence from Stock-Commodity Markets Linkages - Mongi, Arfaoui; Dhouha, Haj Ali (International Journal of Economics and Financial Issues, 2016)
The present paper studies stock-commodity markets linkage using var-garch approach for the period spanning from January 3, 2000 to March 12, 2014. The analysis has been performed through three competing specifications; the var-ccc-garch, the var-bekk-garch, and the var-dcc-garch, ignoring and accounting for structural breaks in volatility to look at the impact of the breaking events on volatility spillovers and its persistence as well as the implications on portfolio management. We found significant interdependency in first and second conditional moments. The structural break dates help forecast current conditional volatility and define its persistence. Their effects have been found slight on optimal weights, miscellaneous on hedge ratios but important on hedging effectiveness. We consider that our findings open up new insights for managerial and governmental policy purposes. Keywords: volatility spillovers, structural breaks, portfolio designs and hedging JEL Classification: F3, F15, G12, Q43